1987
DOI: 10.1002/j.1556-6978.1987.tb00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Process in a Course on Counseling Supervision

Abstract: The learning of supervision implies not only acquisition of formal knowledge but also changes in the learner. Because these changes cannot be completely specified at the outset, the way a supervisor learns must be through a mixture of experiential and didactic teaching. The dialectic between the “inner” and the “outer” learnings required for counselors to change their roles to becoming supervisors forms the substance of this article. Early in the course, the class was fascinated by the seeming inevitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Although empirical research on parallel process may be scant (Friedlander et al, 1989;Martin, Goodyear, & Newton, 1987), clinical experience as a trainer of supervision suggests that it is a powerful concept (Williams, 1987). Indeed, we have observed that a parallel process may be manifest across all three levels (counseling, counselor supervision, and supervisor supervision) and is usually first identified and resolved in supervisor supervision.…”
Section: Counselor-supervisor Process Issuesmentioning
confidence: 83%
See 1 more Smart Citation
“…Although empirical research on parallel process may be scant (Friedlander et al, 1989;Martin, Goodyear, & Newton, 1987), clinical experience as a trainer of supervision suggests that it is a powerful concept (Williams, 1987). Indeed, we have observed that a parallel process may be manifest across all three levels (counseling, counselor supervision, and supervisor supervision) and is usually first identified and resolved in supervisor supervision.…”
Section: Counselor-supervisor Process Issuesmentioning
confidence: 83%
“…By recognizing and labeling repeated patterns, the supervisor can focus on the interpersonal process between the counselor and client; help the counselor identify transference, countertransference, and mutual projections; and assist the counselor in resolving the impasse in the counseling relationship (cf. Williams, 1987). Thus, awareness of parallel process when it exists can shift the focus to more productive content, which can help one avoid unnecessary interpersonal conflict in the supervisory relationship (Mueller & Kell, 1972).…”
Section: Counselor-supervisor Process Issuesmentioning
confidence: 99%
“…Counsellors may enter supervision wanting, yet fearing change (Williams 1987;Deck and Morrow 1989). This fear is compounded if they hold the belief that suggestions for change equal criticism, and they may regard such suggestions as a denunciation of their way of working, thus triggering defensiveness and resistance (Weinbach 1984).…”
Section: Changementioning
confidence: 97%
“…This requires a working knowledge of one's self as well as the aptitude to differentiate one's feelings (Loganbill et al 1982). Interpreting parallel process in a productive way is very challenging, and just highlighting the parallels will not necessarily break the process (Williams 1987). Williams suggests that one strategy in dealing with parallel process is for the supervisor to interpret at length hisher own emotional experience of the counsellor in the supervision relationship and then "Recognising parallel process is difficult."…”
Section: Parallel Processmentioning
confidence: 98%
“…On the basis of their observations of therapists' identifications with their patients in supervision, Sachs and Shapiro (1976) explained, "To tell the therapist that he was unknowingly acting like the patient and identifying with him, was equivalent to accusing the therapist of letting his personal problems interfere with treatment" (p. 412). Furthermore, as the result of his observations of parallel process occurring within a supervision course, Williams (1987) stated that a supervisor's interpretation of the phenomenon to a counselor involved in parallel process is an art, because revealing it too early leads to denial or intellectualizing the situation. These remarks provide further support for the use of MI, because the approach offers an effective way to sidestep counselor defensiveness by using techniques with a spirit of collaboration and "rolling with resistance" (i.e., strategies to decrease defensiveness; Miller & Rollnick, 2002).…”
mentioning
confidence: 97%